PENGARUH DIREKSI WANITA TERHADAP PERATAAN LABA - Dhenta Agusti Widyantoro; Hadi Sumarsono; Dwiati Marsiwi (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
One of the parameters for investors to assess a company is by looking at its earnings. Companies strive to present good and stable earnings, which may lead to the practice of income smoothing. Directors, who have decision-making authority, along with the underlying upper echelon theory that supports the differences in characteristics and gender of women, known for their meticulousness and risk-averse nature, tend to reduce earnings management practices. The objective of this research is to examine the influence of female directors on income smoothing. The research population consists of state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange from 2019 to 2021. The research sample was selected using purposive sampling. Logistic regression analysis was used to test the research data. The results that female directors do not have a significant impact on earnings management. The research includes four control variables, namely cash holding, bonus plan, profitability, and independent commissioners. Cash holding and bonus plan do not have a significant impact on income smoothing. Profitability has a significant negative impact on earnings management, while independent commissioners have a significant positive impact on income smoothing.